A problemática da Dengue, Zika e Chikungunya e a educação ambiental – manual de práticas educativas - Araújo Júnior, José Silvio de Sousa (2020)
The environmental degradation caused and accelerated by urbanization has clear signs that we need to review our relationship with the environment. Any activity that man performs in the environment causes an environmental impact, which unfortunately, most of it is negative. Consequently, there is an increase in the number of diseases in the population, caused by arboviruses such as dengue, zika and chikungunya, transmitted by Aedes aegypti, which has been spreading through tropical and subtropical regions with great intensity. To advance on this problem, environmental education is used as an instrument for the involvement of the school community. In this perspective, this research aimed to develop, through Environmental Education (EA), methodologies for teaching biology related to combating dengue, zika and chikungunya, through a Didactic Sequence (SD). Specifically, to identify students' previous knowledge about AE and diseases caused by Aedes aegypti for subsidiary the construction of a manual; Develop an SD focused on EA and its relationship in combating arboviruses; apply to students and validate a SD; build a manual of educational practices to promote new habits that reflect environmental awareness and that contribute to the endemic control of dengue, zika and chikungunya. For this, a pre-test and a post-test were carried out with students of the 2nd grade of High School, where the results were obtained from the questionnaires and their participation in the execution of different activities. The results inherent to the viability of the didactic sequence that shows an improvement in the students' understanding of the environmental relationship and the arbovirores. The students' statements showed an expansion of concepts, as well as in the post-test records. The students were able to broaden concepts, express that combating arboviruses requires care for the environment, that a partnership between the government and the population is of paramount importance to combat the problem. A Manual of Educational Practices was produced in this research. It presents the didactic sequence, performed by the students. Through this process, students get to know their community and experience Environmental Education through the fight against dengue, zika and chikungunya.